2024 State Flood Plan: History in the Making - Texas Water Development Board (Texas Water Journal)
In August 2024, the Texas Water Development Board adopted the 2024 State Flood Plan, providing the first-ever comprehensive statewide assessment of flood risk and solutions to reduce the risk and impact to life and property due to flooding. The plan incorporates the findings of 15 watershed-based regional flood plans and includes legislative and floodplain management recommendations to guide state, regional, and local flood control policy to reduce the risk and impact of flooding. Senate Bill 8, 86th Texas Legislature (2019), created the regional and state flood planning process modeled after the bottom-up regional and state water planning process. The Texas Water Development Board will produce a new state flood plan every 5 years based on the flood planning groups’ regional plans. This article provides a summary of the 2024 State Flood Plan, and the content is heavily sourced from the published plan.